Power management algorithm for standalone operated renewable distribution generator with hybrid energy backup in microgrid - Veeranjaneyulu Gopu; M.S. Nagaraj (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In a micro grid system during standalone condition the system may not be stable and might not compensate the required load. Especially for renewable source integrated micro grid system grid disconnected condition is more critical as the renewable sources are unpredictable. The renewable distribution generator needs backup module for support to the loads during standalone condition. In this paper complete distribution network with multiple renewable sources which include PV plant, wind plant and fuel cell source is modeled with power management algorithm (PMA) in only photovoltaic (PV) plant. PMA controls the hybrid backup modules supporting the PV DG. The hybrid backup modules considered for the support are battery unit and super capacitor (SC) unit. The battery and SC units charge or discharge as per the PMA controller with respect to power generated by the PV source. The charge and discharge of these units are dependent on PV power, state of charge (SOC) of battery and SOC of SC. These three sources compensate the critical load connected in the micro grid. A comparative analysis is carried out with and without backup modules and PMA during grid islanding condition on the proposed distribution network. All graphical and parametric comparisons are done using MATLAB/ Simulink software with time domain plots generated by PowerGUI tool.